Recent Developments on Silicon Carbide Thin Films for Piezoresistive Sensors Applications - Fraga, Mariana Amorim; Pessoa, Rodrigo Sávio; Maciel, Homero Santiago; Massi, Marcos (IntechOpen, 2011)
None